Green Accounting and Earnings Management In Indonesian Manufacturing Companies - Azizah, Widyaningsih; Fujianti, Lailah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Green accounting and earnings management are two concepts in accounting that have different focuses but can be interrelated in corporate practice. This study was conducted to determine the effect of green accounting implementation on earnings management before and during the COVID-19 pandemic. The research population consists of manufacturing companies listed on the Indonesia Stock Exchange in 2019–2021. The research sample consisted of 159 companies selected through a purposive sampling technique. Data analysis was carried out through regression analysis methods, paired sample t-tests, and the McNemar test. The results showed that there were differences in earnings management practices in the period before and during the COVID-19 pandemic. Meanwhile, green accounting practices before and during the COVID-19 pandemic showed no difference and had no significant effect on earnings management in that period. Significant profitability during the pandemic seems to be more dominant in influencing earnings management than green accounting practices.